ANALYSIS OF THE TRANSFORMATIONAL LEADERSHIP STYLE OF SUB-DISTRICT HEADS AND THE WORK ENVIRONMENT ON THE PERFORMANCE OF NEIGHBORHOOD HEADS WITH WORK MOTIVATION AS AN INTERVENING VARIABLE AT THE MEDAN BARU SUB-DISTRICT OFFICE MEDAN CITY - Ody Rinaldi Sinaga; Desi Astuti; Kholilul Kholik (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of transformational leadership style and work environment on the performance of neighborhood heads with work motivation as an intervening variable at the Medan Baru Subdistrict Office in Medan City. The research problem is motivated by the differences in performance levels among neighborhood heads, which are suspected to be influenced by the subdistrict head's leadership style, work environment conditions, and individual motivation levels. This study uses a quantitative approach with a population of 64 neighborhood heads in Medan Baru Subdistrict, which was used as a saturated sample. Data analysis techniques use Partial Least Squares (PLS) through the SmartPLS 4 program. The results show that transformational leadership has a positive but insignificant effect on the performance of neighborhood heads, but has a positive and significant effect on work motivation. The work environment has a negative and insignificant effect on performance, but a positive and significant effect on work motivation. Work motivation has a positive and significant effect on the performance of neighborhood heads. In addition, work motivation is proven to significantly mediate the relationship between transformational leadership and the work environment on the performance of neighborhood heads. The R² value shows that 81.7% of the variation in work motivation and 95.1% of the variation in performance can be explained by this research model. The research findings confirm that improving the performance of neighborhood heads can be achieved by strengthening work motivation driven by the transformational leadership style of the sub-district head and a conducive work environment. It is recommended that the Medan Baru Sub-District Office strengthen leadership development and attention to employee potential, improve the comfort of the work environment, and provide rewards that encourage work motivation and responsibility.